2018
DOI: 10.1108/ijchm-12-2016-0672
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne illness outbreaks in restaurants and patrons’ propensity to return

Abstract: Purpose This study aims to investigate the decision-making process consumers engage in when choosing to return to a restaurant that has experienced a foodborne illness outbreak. Design/methodology/approach A scenario-based survey was conducted to collect data from 1,025 respondents on their propensity to return to restaurants that have been cited for serving foods that caused a foodborne illness outbreak. Partial least squares-based structural equation modeling was used to analyze the data. Findings The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The composite reliability was examined to confirm consistency among the measurement items for seven constructs (see Table 2). The values of composite reliability for the seven constructs were over 0.60, which confirmed that all measurement items are highly consistent [46]. Furthermore, all average variance extracted (AVE) values exceeded 0.50, which indicated that there was no problem with the convergent validity [47].…”
Section: Measurement Modelmentioning
confidence: 61%
“…The composite reliability was examined to confirm consistency among the measurement items for seven constructs (see Table 2). The values of composite reliability for the seven constructs were over 0.60, which confirmed that all measurement items are highly consistent [46]. Furthermore, all average variance extracted (AVE) values exceeded 0.50, which indicated that there was no problem with the convergent validity [47].…”
Section: Measurement Modelmentioning
confidence: 61%
“…The second part was designed to address the protection intentions of international tourists to use food hygiene indicators in their choice of local restaurant using a seven-point Likert scale, where 1= strongly disagree and 7= strongly agree. Fifteen food hygiene indicators were adopted and adapted from the previous literature (Aksoydan, 2007;Ali et al, 2019;Bai et al, 2019;Barber & Scarcelli, 2009;Barber et al, 2011;Choi et al, 2019;Harris et al, 2018;Henson et al, 2006;Fleetwood, 2019;Park et al, 2016;Yeung &Yee, 2013). The study instrument was given to a panel of experts in the fields of food safety and hospitality management to evaluate the face and content validity of the food hygiene measures.…”
Section: Materials and Methods Survey Instrumentmentioning
confidence: 99%
“…Previous studies also supported different sources of information used by consumers to assess the safety of food and resulting impacts on restaurant selection. These are restaurant inspection notices, press media, and broadcasting, friends and relatives' recommendations, and internet-based information (Ali et al, 2019;Bai et al, 2019;Choi et al, 2013;Choi et al, 2019;Harris et al, 2018;Seo et al, 2015;Uggioni & Salay, 2014;Wong et al, 2015;Yannopoulou et al, 2011).…”
Section: Litrature Review Food Hygiene Cues and Restaurant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is used by the New York City Department of Health and Mental Hygiene (DOHMH) to monitor Yelp for foodborne illness complaints [41,42,43]. It helped food safety regulators improve regulatory efficiency [44].…”
Section: Application Of Online Reviews On Restaurant Improvementmentioning
confidence: 99%